Stanovnici drugih republika i autonomnih pokrajina zaposleni u udruženom radu SR Hrvatske = Inhabitants of other Yugoslav republics and autonomous provinces employed with the organizations of associated labour in SR Croatia - Oliveira-Roca, Maria (Raprave o migracijama = Discussions on migration / Centar za istraživanje migracija Zagreb,, 1981)
Sažetak ; Summary.